Trends in the Diagnosis and Outcomes of Traumatic Carotid and Vertebral Artery Dissections among Medicare Beneficiaries - Newhall, Karina (Ann Vasc Surg, 2016)
BACKGROUND: Early identification of carotid and vertebral artery dissections has been advocated to reduce stroke among trauma patients. We sought to characterize trends in the diagnosis of traumatic carotid and vertebral artery dissections and association changes in stroke rate among Medicare beneficiaries. METHODS: Using Medicare claims, we created a cohort of 5,961 beneficiaries admitted with a new traumatic carotid or vertebral artery dissection from 2001 to 2012. We calculated rates of stroke during hospitalization and 90 days of discharge. We calculated rates of carotid imaging using computed tomography-angiography, carotid duplex, and plain angiography index hospitalization. To study concurrent secular trends, we created a secondary cohort of patients admitted after any traumatic injury from 2001 to 2012 and determined rates of stroke and carotid imaging within this cohort. RESULTS: From 2001 to 2012, incidence of traumatic carotid dissection increased 72% among Medicare beneficiaries (1.1–1.76 per 100,000 patients; rate ratio [RR], 1.72; 95% CI, 1.6–1.9, P < 0.001). Among patients diagnosed with traumatic carotid or vertebral artery dissections, the combined in-hospital and 90-day stroke rate did not change significantly (4.9% in 2001; 5.2% in 2012; RR, 1.06; 95% CI, 0.93–1.20; P = 0.094). Likewise, there was little change in mortality (10.3%; RR, 1.01; 95% CI, 0.95–1.06; P = 0.88). Among all trauma patients, the use of computed tomography angiography has increased 16-fold (2–35 per 100,000 patients; RR, 16.7; 95% CI, 13–19; P < 0.0001). CONCLUSIONS: Despite increased diagnosis of carotid or vertebral artery dissection, there has been little change in stroke risk among trauma patients. Efforts to more effectively target imaging and treatment for these patients are necessary.